Metal-based wear-resistant self-lubricating coating material and preparation method and application thereof

By performing high-temperature pretreatment on cBN powder to generate cBN+hBN coexistence powder, and mixing it with alloy powder, the coating is prepared using laser cladding method, which solves the problem of increased friction coefficient of existing coatings when hardness and wear resistance are improved. , achieving both wear resistance and friction-reducing properties.

CN118756137BActive Publication Date: 2025-01-24TIANJIN UNIV OF TECH & EDUCATION (TEACHER DEV CENT OF CHINA VOCATIONAL TRAINING & GUIDANCE)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411241839.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-24
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

When the existing metal-based ceramic reinforced phase composite coatings improve hardness and wear resistance, the friction coefficient increases, and the addition of solid lubricant is prone to burn at high temperatures, resulting in a degradation of coating performance.

Method used

By conducting high -temperature pre -treatment of cubic boron nitride (CBN) powder, the surface is converted into hexagonal boron nitride (HBN), generates the coexistence of CBN+HBN, and mix it with the alloy powder to prepare with the laser melting method. Metal-wear-resistant self-lubricating coating.

Benefits of technology

The abrasion resistance and reduction performance of the coating are realized, the problem of rising friction coefficients is avoided, and the dependence on the solid lubricant is reduced, and the stability of the coating performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118756137B_ABST
    Figure CN118756137B_ABST
Patent Text Reader

Abstract

The present invention discloses a metal-based wear-resistant self-lubricating coating material, a preparation method and an application thereof. The method of the present invention comprises the following steps: step (1) preparing wear-resistant self-lubricating powder; the wear-resistant self-lubricating powder is a powder obtained by vacuum heating pretreatment of cubic boron nitride powder; step (2) preparing coating material: the wear-resistant self-lubricating powder and alloy powder are mixed evenly, dried, and a coating material is obtained; step (3) the coating material is arranged on the surface of a base material, and a metal-based wear-resistant self-lubricating coating material is prepared on the base material by laser cladding. The present invention adopts a high-temperature pretreatment method to convert the surface of cBN particles into hBN, and generate cBN+hBN powder (wear-resistant self-lubricating powder) in different proportions; the above-mentioned powder has the characteristics of integrated wear resistance and friction reduction. By adding this powder, the preparation of a coating material with relatively good hardness and friction reduction performance can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating preparation, and in particular to a metal-based wear-resistant self-lubricating coating material and a preparation method and application thereof. Background Art

[0002] Surface modification technology is a method of physically, chemically or mechanically treating the surface of a material to improve its wear resistance, corrosion resistance, thermal conductivity and other properties to adapt to different environments and needs.

[0003] Among the many surface modification technologies such as spraying, laser cladding, and surfacing, high-performance coatings are mainly prepared on the workpiece surface by using different types of powder systems to improve the problem of insufficient surface performance of the workpiece. Among them, the preparation of wear-resistant coatings has attracted the attention of many researchers.

[0004] Cubic boron nitride (cBN), as a ceramic reinforcement phase, is a new type of ceramic material. Its hardness is second only to diamond and it is a superhard material. Due to its outstanding properties such as high strength, high hardness, good corrosion resistance, good wear resistance, good heat resistance and high chemical resistance, it has become one of the most promising reinforcement materials in engineering applications.

[0005] In current research, metal-based ceramic reinforced phase composite coatings show excellent wear resistance due to their high hardness, but the increase in friction coefficient caused by the addition of ceramic reinforcement phases has been ignored. The addition of general ceramic materials can only improve the hardness and wear resistance of the coating, but the effect on reducing friction is not obvious and may even lead to an increase in the friction coefficient. Some studies will choose to add solid lubricants such as graphene, MoS2, WS2, etc. to solve the above problems. However, due to the low melting point of such materials, they are easily burned at high temperatures and are difficult to retain in the coating to play their role. At the same time, some compounds that cause the coating performance to deteriorate may also be generated. In addition, graphene, MoS2, WS2, etc. have small particle sizes and large surface energy. Directly adding them to the coating will cause problems such as powder agglomeration.

[0006] Therefore, it is necessary to prepare a coating material with good hardness and friction reduction properties. Summary of the invention

[0007] The purpose of the present invention is to provide a metal-based wear-resistant self-lubricating coating material and a preparation method and application. Cubic boron nitride (cBN) can be converted into hexagonal boron nitride (hBN) at about 1300°C. The present invention uses a high-temperature pretreatment method to convert the surface of cBN particles into hBN, generating cBN+hBN powders (wear-resistant self-lubricating powders) in different proportions; the cubic boron nitride (cBN) therein can be used as a coating material reinforcement particle, because cBN has extremely high hardness and excellent wear resistance, and the hexagonal boron nitride (hBN) therein has excellent friction reduction performance. Therefore, the above-mentioned powder has the characteristics of wear resistance (cBN has the characteristics of high hardness) and friction reduction (hBN is a solid lubricant) integrated. The present invention adds the above-mentioned wear-resistant self-lubricating powder to the metal-based powder in a certain proportion, which can realize the preparation of a coating material with relatively good hardness and friction reduction performance.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] The first aspect of the present invention is to provide a method for preparing a metal-based wear-resistant self-lubricating coating material, comprising the following steps:

[0010] Step (1) preparing wear-resistant self-lubricating powder; the wear-resistant self-lubricating powder is a cubic boron nitride powder pre-treated by vacuum heating;

[0011] Step (2) preparing a coating material: uniformly mixing the wear-resistant self-lubricating powder and the alloy powder, and drying to obtain a coating material;

[0012] Step (3) sets the coating material on the surface of the base material, and prepares a metal-based wear-resistant self-lubricating coating material on the base material by laser cladding.

[0013] In the prior art, the surface of cBN powder and alloy powder is directly laser clad to prepare the coating, but the heat input temperature in the laser cladding is too high, and it is difficult to accurately control the occurrence of the conversion from cBN to hBN, so it is difficult to control the content and uniformity of the distribution of hBN in the coating, and thus it is difficult to ensure the stability of the coating performance. However, the present invention pre-treats the cBN powder at a high temperature so that the surface of the cBN powder is converted into hBN, so that the single cBN powder becomes a powder in which cBN and hBN coexist after the pre-treatment (i.e., a wear-resistant self-lubricating powder is prepared). Then, the above-mentioned cBN and hBN coexisting powder is mixed evenly with the alloy powder and then input at a high temperature as a coating material to prepare the coating. Since the surface of the cBN powder in the above-mentioned cBN and hBN coexisting powder has been converted into hBN after high-temperature treatment, when it is laser clad, basically not too much cBN powder will be converted into hBN, so that the content and uniformity of the distribution of hBN in the coating can be effectively controlled, and thus it is difficult to ensure the stability of the coating performance.

[0014] As a preferred embodiment,

[0015] Step (1), the particle size of the cubic boron nitride powder is in the range of 10-53 μm; preferably selected from 10-20 μm, 20-30 μm or 35-53 μm; and / or,

[0016] The vacuum heating pretreatment is performed at 1200-1400°C for 1.5h-2h; and / or, for example, the vacuum heating pretreatment temperature is 1200, 1300, 1400°C;

[0017] The vacuum degree of the vacuum heating pretreatment is 30-40KPa; and / or,

[0018] The heating rate of the vacuum heating pretreatment is 10°C / min-18°C / min; the cooling rate is 3°C / min-7°C / min.

[0019] As a preferred embodiment,

[0020] Step (2),

[0021] The alloy powder is at least one of CoCrNi, CoCrFeNi, CoCrFeNiTi, Ti60, and Fe60 alloy systems; and / or,

[0022] The coating material comprises 15-20wt% of wear-resistant self-lubricating powder and 80-85wt% of alloy powder; and / or,

[0023] The particle size of the alloy powder is 15-53 μm; and / or,

[0024] The alloy powder and the wear-resistant self-lubricating powder are mixed uniformly by ball milling together.

[0025] As a preferred embodiment,

[0026] The ball milling speed is 300-600 rpm; and / or,

[0027] The ball milling time is 1.5h-3h; and / or,

[0028] The ball-to-material mass ratio is 1-10:1; and / or,

[0029] The drying temperature is 100°C-120°C.

[0030] As a preferred embodiment,

[0031] In step (3), laser cladding includes the following steps:

[0032] Step (a): placing a laser head on the surface of the base material to be clad;

[0033] Step (b): conveying the coating material to the surface of the substrate material to be clad;

[0034] Step (c): The laser head emits a laser to the surface of the base material to be clad with the coating material, so as to prepare a metal-based wear-resistant self-lubricating coating material on the surface of the base material.

[0035] In the technical solution of the present invention, the matrix material is not limited, and the effect is better when it is made of titanium alloy, and TC11 titanium alloy is preferred.

[0036] As a preferred embodiment,

[0037] In step (a), the laser head is offset in the X-axis direction and is aligned with the surface of the substrate to be clad. and / or,

[0038] The distance between the laser head and the surface of the base material to be clad is 16-20 mm; and / or,

[0039] Step (b), the coating material flow rate is 12-14.2 g / min; and / or,

[0040] Step (c), the laser power is 1800W-2300W; and / or,

[0041] The wavelength of the laser is 635-650nm; and / or,

[0042] During laser cladding, the substrate material used is a preheated substrate at a preheating temperature of 400°C-600°C.

[0043] In the present invention, the base material used can be any base material commonly used in existing laser cladding.

[0044] As a preferred embodiment,

[0045] The mass content of hexagonal boron nitride in the wear-resistant self-lubricating powder is 10-40%.

[0046] As a preferred embodiment,

[0047] The mass content of hexagonal boron nitride in the wear-resistant self-lubricating powder is 15-30%.

[0048] The second aspect of the present invention is to provide a metal-based wear-resistant self-lubricating coating material prepared by the method described in the first aspect of the present invention.

[0049] The second aspect of the present invention is to provide the application of the metal-based wear-resistant self-lubricating coating material prepared by the method described in the first aspect of the present invention in the fields of aerospace, shipbuilding and automobile.

[0050] The beneficial effects of the present invention are as follows:

[0051] The present invention uses high temperature to perform surface pretreatment on cBN, so that the surface of the cBN powder is transformed to become a powder in which cBN and hBN coexist. The two powders have good bonding properties, and hBN is distributed on the surface of cBN. cBN is a micron-level powder with good dispersibility and will not agglomerate. By adding this powder, wear-resistant (cBN) and friction-reducing (hBN) coatings can be prepared, effectively solving the problem of unstable coating performance caused by directly introducing cBN powder in the existing laser cladding process.

[0052] The coating of the present invention uses only one cBN powder as the starting material to achieve wear reduction and wear resistance integration without the need to add other solid lubricants, so that a coating with better performance can be obtained; compared with the prior art, the use of other friction-reducing powders can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is a powder Raman spectrum of cubic boron nitride powder of Example 6 of the present invention before vacuum heating pretreatment;

[0054] Figure 2 This is a powder Raman spectrum of cubic boron nitride powder after vacuum heating pretreatment in Example 6 of the present invention;

[0055] Figure 3 This is the XRD pattern of the metal-based wear-resistant self-lubricating coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0056] The present invention is further described in detail below through the accompanying drawings and specific embodiments.

[0057] Example 1

[0058] Preparation of wear-resistant self-lubricating powder: Pre-treat cubic boron nitride (cBN) powder in a vacuum heat treatment furnace. The specific steps are as follows: spread 10-20μm cBN on a glass dish, put the glass dish containing cBN powder into a vacuum heat treatment furnace, set the temperature to 1200℃, set the heating rate to 10℃ / min, keep warm for 2h, and the cooling rate to 3℃ / min. The above steps need to be carried out in a vacuum (vacuum degree is 30KPa).

[0059] Laser cladding: This patent will be based on (CoCrNi) 94The preparation of Al3Ti3-cBN composite coating is introduced as an example. CoCrNi medium entropy alloy (spherical powder with a particle size of 15-53μm and a purity of 99%) is mixed with wear-resistant self-lubricating powder (cBN powder after pretreatment), and ball milled in a planetary ball mill for 1.5h, with a ball-to-material mass ratio of 1:1 and a rotation speed of 300rpm; the mixed powder is dried at 100℃ for 30min in a drying oven and cooled to room temperature to obtain a coating material; the content of wear-resistant self-lubricating powder in the coating material is 15wt%.

[0060] The embodiment adopts the laser cladding method to prepare the composite coating on the TC11 substrate, and uses the coaxial powder feeding method to prepare the coating; the shielding gas uses the inert gas argon (purity 99.999%), the powder feeding amount is selected to be 12g / min, the shielding gas flow rate is 12L / min, and the TC11 is preheated at a preheating temperature of 400°C. The fiber laser cladding equipment is used to prepare the coating. After the laser head is aligned with the surface to be clad of the TC11 alloy through the robot controller, the laser head is slightly tilted, and the laser head is offset in the X-axis direction, so that it is at a certain angle with the surface to be clad. ; Use the robot controller to adjust the distance between the laser head and the substrate surface so that the defocus between the laser head and the substrate surface (i.e., the distance between the laser head and the substrate surface) is always maintained at 20 mm. At this time, the powder can be guaranteed to converge at the intersection of the laser beam convergence point, and the coating overlap rate is set. The optimal forming quality of the present invention is selected to have an overlap rate of 85%. Turn on the high-speed reciprocating platform and set the reciprocating platform moving speed to 240 mm / s. Select external control, and the powder feeding switch is controlled by the program in the robot controller; Set the laser power in the laser system to 1800 W (the wavelength of the laser is 635 nm), and the light waiting time is set to 2s. After completing the above steps, start the program to prepare the composite coating. Observe the powder feeder, protective gas and laser system during the cladding process. After completing the above steps, a composite coating that takes into account both hardness and lubrication properties is obtained, that is, a metal-based-wear-resistant self-lubricating coating, and its XRD pattern is as shown below. Figure 3 shown.

[0061] from Figure 3 It can be seen that there is not only cBN but also hBN in the coating. In addition, the coating is a dual phase of FCC and BCC. As is known to all, the CoCrNi medium entropy alloy is a single phase of FCC. The reason why the dual phases of FCC and BCC are produced in the coating of the present invention is mainly because cBN reacts with the metal powder. According to existing reports, the performance of the coating with FCC+BCC is better than that of the single phase of FCC. In addition, the coating of the present invention has also been proven to contain TiN, which is a ceramic reinforcement phase with higher hardness, which can further enhance the performance of the coating. The appearance of Ti mainly comes from the TC11 substrate.

[0062] Example 2

[0063] Preparation of wear-resistant self-lubricating powder: Pre-treat cubic boron nitride (cBN) powder in a vacuum heat treatment furnace. The specific steps are as follows: spread 10-20μm cBN on a glass dish, put the glass dish containing cBN powder into a vacuum heat treatment furnace, set the temperature to 1300℃, set the heating rate to 14℃ / min, keep warm for 1.8h, and the cooling rate is 5℃ / min. The above steps need to be carried out in a vacuum (vacuum degree is 35KPa).

[0064] Laser cladding: This patent will be based on (CoCrNi) 94 The preparation of Al3Ti3-cBN composite coating is introduced as an example. CoCrNi medium entropy alloy (spherical powder with a particle size of 15-53μm and a purity of 99%) is mixed with wear-resistant self-lubricating powder (pretreated cBN powder), and ball milled in a planetary ball mill for 1.8h, with a ball-to-material mass ratio of 6:1 and a rotation speed of 450rpm; the mixed powder is dried at 110℃ for 30min in a drying oven and cooled to room temperature to obtain a coating material; the content of wear-resistant self-lubricating powder in the coating material is 18wt%.

[0065] The embodiment adopts the laser cladding method to prepare the composite coating on the TC11 substrate, and uses the coaxial powder feeding method to prepare the coating; the shielding gas uses the inert gas argon (purity 99.999%), the powder feeding amount is selected to be 12.6 g / min, the shielding gas flow rate is 12L / min, and the TC11 is preheated at a preheating temperature of 500°C. The fiber laser cladding equipment is used to prepare the coating. After the laser head is aligned with the surface to be clad of the TC11 alloy through the robot controller, the laser head is slightly tilted, and the laser head is offset in the X-axis direction, so that it is at a certain angle with the surface to be clad. ; Use the robot controller to adjust the distance between the laser head and the substrate surface so that the defocus between the laser head and the substrate surface is always maintained at 18mm. At this time, the powder can be guaranteed to converge at the intersection of the laser beam convergence point, and the coating overlap rate is set. The optimal forming quality of the present invention selects an overlap rate of 88%. Turn on the high-speed reciprocating platform to set the platform movement speed. The selected speed is 230mm / s. Select external control, and the powder feeding switch is controlled by the program in the robot controller; Set the laser power in the laser system to 2100W (the wavelength of the laser is 640nm), and the light waiting time is set to 2s. After completing the above steps, start the program to prepare the composite coating. Observe the powder feeder, protective gas and laser system during the cladding process. After completing the above steps, a composite coating that takes into account both hardness and lubrication properties is obtained, that is, a metal-based-wear-resistant self-lubricating coating.

[0066] Example 3

[0067] Preparation of wear-resistant self-lubricating powder: Pre-treat cubic boron nitride (cBN) powder in a vacuum heat treatment furnace. The specific steps are as follows: spread 10-20μm cBN on a glass dish, put the glass dish containing cBN powder into a vacuum heat treatment furnace, set the temperature to 1400℃, set the heating rate to 18℃ / min, keep warm for 1.5h, and the cooling rate is 7℃ / min. The above steps need to be carried out in a vacuum (vacuum degree is 40KPa).

[0068] Laser cladding: This patent will be based on (CoCrNi) 94 The preparation of Al3Ti3-cBN composite coating is introduced as an example. CoCrNi medium entropy alloy (spherical powder with a particle size of 15-53μm and a purity of 99%) is mixed with wear-resistant self-lubricating powder (pretreated cBN powder), and ball milled in a planetary ball mill for 2h, with a ball-to-material mass ratio of 10:1 and a rotation speed of 600rpm; the mixed powder is dried at 120℃ for 30min in a drying oven and cooled to room temperature to obtain a coating material; the content of wear-resistant self-lubricating powder in the coating material is 20wt%.

[0069] The embodiment adopts the laser cladding method to prepare the composite coating on the TC11 substrate, and uses the coaxial powder feeding method to prepare the coating; the shielding gas uses the inert gas argon (purity 99.999%), the powder feeding amount is selected to be 13g / min, the shielding gas flow rate is 12L / min, and the TC11 is preheated at a preheating temperature of 600°C. The fiber laser cladding equipment is used to prepare the coating. After the laser head is aligned with the surface to be clad of the TC11 alloy through the robot controller, the laser head is slightly tilted, and the laser head is offset in the X-axis direction, so that it is at a certain angle with the surface to be clad. ; Use the robot controller to adjust the distance between the laser head and the substrate surface so that the defocus between the laser head and the substrate surface is always maintained at 16mm. At this time, the powder can be guaranteed to converge at the intersection of the laser beam convergence point, set the coating overlap rate, and the optimal forming quality of the present invention is selected to have an overlap rate of 90%. Turn on the high-speed reciprocating platform to set the platform movement speed. The selected speed is 220mm / s. Select external control, and the powder feeding switch is controlled by the program in the robot controller; Set the laser power in the laser system to 2300W (the wavelength of the laser is 650nm), and the light waiting time is set to 2s. After completing the above steps, start the program to prepare the composite coating. Observe the powder feeder, protective gas and laser system during the cladding process. After completing the above steps, a composite coating that takes into account both hardness and lubrication properties is obtained, that is, a metal-based wear-resistant self-lubricating coating.

[0070] Example 4

[0071] Preparation of wear-resistant self-lubricating powder: Pre-treat cubic boron nitride (cBN) powder in a vacuum heat treatment furnace. The specific steps are as follows: spread 20-30μm cBN on a glass dish, put the glass dish containing cBN powder into a vacuum heat treatment furnace, set the temperature to 1200℃, set the heating rate to 10℃ / min, keep warm for 2h, and the cooling rate is 3℃ / min. The above steps need to be carried out in a vacuum (vacuum degree is 30 KPa).

[0072] Laser cladding: This patent will be based on (CoCrNi) 94 The preparation of Al3Ti3-cBN composite coating is introduced as an example. CoCrNi medium entropy alloy (spherical powder with a particle size of 15-53μm and a purity of 99%) is mixed with wear-resistant self-lubricating powder (pretreated cBN powder), and ball milled in a planetary ball mill for 2h, with a ball-to-material mass ratio of 10:1 and a rotation speed of 600rpm; the mixed powder is dried at 120℃ for 30min in a drying oven and cooled to room temperature to obtain a coating material; the content of wear-resistant self-lubricating powder in the coating material is 20wt%.

[0073] The embodiment adopts the laser cladding method to prepare the composite coating on the TC11 substrate, and uses the coaxial powder feeding method to prepare the coating; the shielding gas uses the inert gas argon (purity 99.999%), the powder feeding amount is selected to be 13.5g / min, the shielding gas flow rate is 12L / min, and the TC11 is preheated at a preheating temperature of 600°C. The fiber laser cladding equipment is used to prepare the coating. After the laser head is aligned with the surface to be clad of the TC11 alloy through the robot controller, the laser head is slightly tilted, and the laser head is offset in the X-axis direction, so that it is at a certain angle with the surface to be clad. ; Use the robot controller to adjust the distance between the laser head and the substrate surface so that the defocus between the laser head and the substrate surface is always maintained at 16mm. At this time, the powder can be guaranteed to converge at the intersection of the laser beam convergence point, set the coating overlap rate, and the optimal forming quality of the present invention is selected to have an overlap rate of 90%. Turn on the high-speed reciprocating platform to set the platform movement speed. The selected speed is 220mm / s. Select external control, and the powder feeding switch is controlled by the program in the robot controller; Set the laser power in the laser system to 2300W (the wavelength of the laser is 650nm), and the light waiting time is set to 2s. After completing the above steps, start the program to prepare the composite coating. Observe the powder feeder, protective gas and laser system during the cladding process. After completing the above steps, a composite coating that takes into account both hardness and lubrication properties is obtained, that is, a metal-based wear-resistant self-lubricating coating.

[0074] Example 5

[0075] Preparation of wear-resistant self-lubricating powder: Pre-treat cubic boron nitride (cBN) powder in a vacuum heat treatment furnace. The specific steps are as follows: spread 20-30μm cBN on a glass dish, put the glass dish containing cBN powder into a vacuum heat treatment furnace, set the temperature to 1300℃, set the heating rate to 14℃ / min, keep warm for 1.8h, and the cooling rate is 5℃ / min. The above steps need to be carried out in a vacuum (vacuum degree is 35 KPa).

[0076] Laser cladding: This patent will be based on (CoCrNi) 94 The preparation of Al3Ti3-cBN composite coating is introduced as an example. CoCrNi medium entropy alloy (spherical powder with a particle size of 15-53μm and a purity of 99%) is mixed with wear-resistant self-lubricating powder (pretreated cBN powder), and ball milled in a planetary ball mill for 1.8h, with a ball-to-material mass ratio of 6:1 and a rotation speed of 450rpm; the mixed powder is dried at 110℃ for 30min in a drying oven and cooled to room temperature to obtain a coating material; the content of wear-resistant self-lubricating powder in the coating material is 18wt%,

[0077] The embodiment adopts the laser cladding method to prepare the composite coating on the TC11 substrate, and uses the coaxial powder feeding method to prepare the coating; the shielding gas uses the inert gas argon (purity 99.999%), the powder feeding amount is selected to be 13.2g / min, the shielding gas flow rate is 12L / min, and the TC11 is preheated at a preheating temperature of 500°C. The fiber laser cladding equipment is used to prepare the coating. After the laser head is aligned with the surface to be clad of the TC11 alloy through the robot controller, the laser head is slightly tilted, and the laser head is offset in the X-axis direction, so that it is at a certain angle with the surface to be clad. ; Use the robot controller to adjust the distance between the laser head and the substrate surface so that the defocus between the laser head and the substrate surface is always maintained at 18 mm. At this time, the powder can be ensured to converge at the intersection of the laser beam convergence point, set the coating overlap rate, and the optimal forming quality of the present invention is selected to have an overlap rate of 88%. Turn on the high-speed reciprocating platform to set the platform moving speed. The selected speed is 230mm / s. Select external control, and the powder feeding switch is controlled by the program in the robot controller; Set the laser power in the laser system to 2100W (the wavelength of the laser is 640nm), and the light waiting time is set to 2s. After completing the above steps, start the program to prepare the composite coating. Observe the powder feeder, protective gas and laser system during the cladding process. After completing the above steps, a composite coating that takes into account both hardness and lubrication properties is obtained, that is, a metal-based wear-resistant self-lubricating coating.

[0078] Example 6

[0079] Preparation of wear-resistant self-lubricating powder: Pre-treat cubic boron nitride (cBN) powder in a vacuum heat treatment furnace. The specific steps are as follows: spread 20-30μm cBN on a glass dish, put the glass dish containing cBN powder into a vacuum heat treatment furnace, set the temperature to 1400℃, set the heating rate to 18℃ / min, keep warm for 1.5h, and cool down at a rate of 7℃ / min. The above steps need to be carried out in a vacuum (vacuum degree is 40 KPa). The Raman spectra of the powder before and after vacuum heat treatment are as follows: Figure 1 and Figure 2 As shown, it can be seen that hBN appears on the surface of cBN.

[0080] Laser cladding: This patent will be based on (CoCrNi) 94 The preparation of Al3Ti3-cBN composite coating is introduced as an example. CoCrNi medium entropy alloy (spherical powder with a particle size of 15-53μm and a purity of 99%) is mixed with wear-resistant self-lubricating powder (cBN powder after pretreatment), and ball milled in a planetary ball mill for 1.5h, with a ball-to-material mass ratio of 1:1 and a rotation speed of 300rpm; the mixed powder is dried at 100℃ for 30min in a drying oven and cooled to room temperature to obtain a coating material; the content of wear-resistant self-lubricating powder in the coating material is 15wt%.

[0081] The embodiment adopts the laser cladding method to prepare the composite coating on the TC11 substrate, and uses the coaxial powder feeding method to prepare the coating; the shielding gas uses the inert gas argon (purity 99.999%), the powder feeding amount is selected to be 12.6g / min, the shielding gas flow rate is 12L / min, and the TC11 is preheated at a preheating temperature of 400°C. The fiber laser cladding equipment is used to prepare the coating. After the laser head is aligned with the surface to be clad of the TC11 alloy through the robot controller, the laser head is slightly tilted, and the laser head is offset in the X-axis direction, so that it is at a certain angle with the surface to be clad. ; Use the robot controller to adjust the distance between the laser head and the substrate surface so that the defocus between the laser head and the substrate surface is always maintained at 20mm. At this time, the powder can be guaranteed to converge at the intersection of the laser beam convergence point, and the coating overlap rate is set. The optimal forming quality of the present invention selects an overlap rate of 85%. Turn on the high-speed reciprocating platform to set the platform movement speed. The selected speed is 240mm / s. Select external control, and the powder feeding switch is controlled by the program in the robot controller; Set the laser power in the laser system to 1800W (the wavelength of the laser is 635nm), and the light waiting time is set to 2s. After completing the above steps, start the program to prepare the composite coating. Observe the powder feeder, protective gas and laser system during the cladding process. After completing the above steps, a composite coating that takes into account both hardness and lubrication properties is obtained, that is, a metal-based-wear-resistant self-lubricating coating.

[0082] Example 7

[0083] Preparation of wear-resistant self-lubricating powder: Pre-treat cubic boron nitride (cBN) powder in a vacuum heat treatment furnace. The specific steps are as follows: spread 35-53μm cBN on a glass dish, put the glass dish containing cBN powder into a vacuum heat treatment furnace, set the temperature to 1200℃, set the heating rate to 10℃ / min, keep warm for 2h, and the cooling rate is 3℃ / min. The above steps need to be carried out in a vacuum (vacuum degree is 30 KPa).

[0084] Laser cladding: This patent will be based on (CoCrNi) 94 The preparation of Al3Ti3-cBN composite coating is introduced as an example. CoCrNi medium entropy alloy (spherical powder with a particle size of 15-53μm and a purity of 99%) is mixed with wear-resistant self-lubricating powder (cBN powder after pretreatment), and ball milled in a planetary ball mill for 1.5h, with a ball-to-material mass ratio of 1:1 and a rotation speed of 300rpm; the mixed powder is dried at 100℃ for 30min in a drying oven and cooled to room temperature to obtain a coating material; the content of wear-resistant self-lubricating powder in the coating material is 15wt%.

[0085] The embodiment adopts the laser cladding method to prepare the composite coating on the TC11 substrate, and uses the coaxial powder feeding method to prepare the coating; the shielding gas uses the inert gas argon (purity 99.999%), the powder feeding amount is selected to be 12.9g / min, the shielding gas flow rate is 12L / min, and the TC11 is preheated at a preheating temperature of 400°C. The fiber laser cladding equipment is used to prepare the coating. After the laser head is aligned with the surface to be clad of the TC11 alloy through the robot controller, the laser head is slightly tilted, and the laser head is offset in the X-axis direction, so that it is at a certain angle with the surface to be clad. ; Use the robot controller to adjust the distance between the laser head and the substrate surface so that the defocus between the laser head and the substrate surface is always maintained at 20mm. At this time, the powder can be guaranteed to converge at the intersection of the laser beam convergence point, and the coating overlap rate is set. The optimal forming quality of the present invention selects an overlap rate of 85%. Turn on the high-speed reciprocating platform to set the platform movement speed. The selected speed is 240mm / s. Select external control, and the powder feeding switch is controlled by the program in the robot controller; Set the laser power in the laser system to 1800W (the wavelength of the laser is 635nm), and the light waiting time is set to 2s. After completing the above steps, start the program to prepare the composite coating. Observe the powder feeder, protective gas and laser system during the cladding process. After completing the above steps, a composite coating that takes into account both hardness and lubrication properties is obtained, that is, a metal-based-wear-resistant self-lubricating coating.

[0086] Example 8

[0087] Preparation of wear-resistant self-lubricating powder: Pre-treat cubic boron nitride (cBN) powder in a vacuum heat treatment furnace. The specific steps are as follows: spread 35-53μm cBN on a glass dish, put the glass dish containing cBN powder into a vacuum heat treatment furnace, set the temperature to 1300℃, set the heating rate to 14℃ / min, keep warm for 1.8h, and the cooling rate is 5℃ / min. The above steps need to be carried out in a vacuum (vacuum degree is 35 KPa).

[0088] Laser cladding: This patent will be based on (CoCrNi) 94 The preparation of Al3Ti3-cBN composite coating is introduced as an example. CoCrNi medium entropy alloy (spherical powder with a particle size of 15-53μm and a purity of 99%) is mixed with wear-resistant self-lubricating powder (pretreated cBN powder), and ball milled in a planetary ball mill for 1.8h, with a ball-to-material mass ratio of 6:1 and a rotation speed of 450rpm; the mixed powder is dried at 110℃ for 30min in a drying oven and cooled to room temperature to obtain a coating material; the content of wear-resistant self-lubricating powder in the coating material is 18wt%.

[0089] The embodiment adopts the laser cladding method to prepare the composite coating on the TC11 substrate, and uses the coaxial powder feeding method to prepare the coating; the shielding gas uses the inert gas argon (purity 99.999%), the powder feeding amount is selected to be 13.7g / min, the shielding gas flow rate is 12L / min, and the TC11 is preheated at a preheating temperature of 500°C. The fiber laser cladding equipment is used to prepare the coating. After the laser head is aligned with the surface to be clad of the TC11 alloy through the robot controller, the laser head is slightly tilted, and the laser head is offset in the X-axis direction, so that it is at a certain angle with the surface to be clad. ; Use the robot controller to adjust the distance between the laser head and the substrate surface so that the defocus between the laser head and the substrate surface is always maintained at 18mm. At this time, the powder can be guaranteed to converge at the intersection of the laser beam convergence point, and the coating overlap rate is set. The optimal forming quality of the present invention selects an overlap rate of 88%. Turn on the high-speed reciprocating platform to set the platform movement speed. The selected speed is 230mm / s. Select external control, and the powder feeding switch is controlled by the program in the robot controller; Set the laser power in the laser system to 2100W (the wavelength of the laser is 640nm), and the light waiting time is set to 2s. After completing the above steps, start the program to prepare the composite coating. Observe the powder feeder, protective gas and laser system during the cladding process. After completing the above steps, a composite coating that takes into account both hardness and lubrication properties is obtained, that is, a metal-based-wear-resistant self-lubricating coating.

[0090] Example 9

[0091] Preparation of wear-resistant self-lubricating powder: Cubic boron nitride (cBN) powder is pretreated in a vacuum heat treatment furnace. The specific steps are as follows: 35-53μm cBN is spread flat on a glass dish, and the glass dish containing cBN powder is placed in a vacuum heat treatment furnace. The temperature is set to 1400℃, the heating rate is set to 18℃ / min, the temperature is kept for 1.5h, and the cooling rate is 7℃ / min. The above steps need to be carried out in a vacuum (vacuum degree is 40 KPa).

[0092] Laser cladding: This patent will be based on (CoCrNi) 94 The preparation of Al3Ti3-cBN composite coating is introduced as an example. CoCrNi medium entropy alloy (spherical powder with a particle size of 15-53μm and a purity of 99%) is mixed with wear-resistant self-lubricating powder (pretreated cBN powder), and ball milled in a planetary ball mill for 2h, with a ball-to-material mass ratio of 10:1 and a rotation speed of 600rpm; the mixed powder is dried at 120℃ for 30min in a drying oven and cooled to room temperature to obtain a coating material; the content of wear-resistant self-lubricating powder in the coating material is 20wt%.

[0093] The embodiment adopts the laser cladding method to prepare the composite coating on the TC11 substrate, and uses the coaxial powder feeding method to prepare the coating; the shielding gas uses the inert gas argon (purity 99.999%), the powder feeding amount is selected to be 14.2g / min, the shielding gas flow rate is 12L / min, and the TC11 is preheated at a preheating temperature of 600°C. The fiber laser cladding equipment is used to prepare the coating. After the laser head is aligned with the surface to be clad of the TC11 alloy through the robot controller, the laser head is slightly tilted, and the laser head is offset in the X-axis direction, so that it is at a certain angle with the surface to be clad. ; Use the robot controller to adjust the distance between the laser head and the substrate surface so that the defocus between the laser head and the substrate surface is always maintained at 16mm. At this time, the powder can be guaranteed to converge at the intersection of the laser beam convergence point, set the coating overlap rate, and the optimal forming quality of the present invention is selected to have an overlap rate of 90%. Turn on the high-speed reciprocating platform to set the platform movement speed. The selected speed is 220mm / s. Select external control, and the powder feeding switch is controlled by the program in the robot controller; Set the laser power in the laser system to 2300W (the wavelength of the laser is 650nm), and the light waiting time is set to 2s. After completing the above steps, start the program to prepare the composite coating. Observe the powder feeder, protective gas and laser system during the cladding process. After completing the above steps, a composite coating that takes into account both hardness and lubrication properties is obtained, that is, a metal-based wear-resistant self-lubricating coating.

[0094] Comparative Example 1

[0095] The preparation method is basically the same as that of Example 1, except that the preparation of the wear-resistant self-lubricating powder in step (1) is not performed, and the cubic boron nitride powder and the alloy powder are directly mixed uniformly in the manner of step (2) of Example 1.

[0096] Comparative Example 2

[0097] The preparation method is basically the same as that of Example 1, except that step (1) preparation of wear-resistant self-lubricating powder and step (2) preparation of coating material are not performed, and CoCrNi medium entropy alloy (spherical powder with a particle size of 15-53 μm and a purity of 99%) is directly laser clad in the manner of step (3) of Example 1.

[0098] The coating properties of the above embodiments or comparative examples are shown in Table 1 below.

[0099] Table 1

[0100]

[0101] The smaller the friction coefficient, the better the friction reduction effect.

[0102] It can be seen from the results in Table 1 that the preparation of a wear-resistant and friction-reducing coating can be achieved by adding the wear-resistant self-lubricating powder of the present invention.

[0103] By comparing Example 1 with Comparative Example 1, it can be seen that the hardness and friction reduction effect of the coating prepared by laser cladding of the wear-resistant self-lubricating powder first prepared by the present invention and then mixed with the alloy powder as a coating material are better than those of the coating prepared in Comparative Example 1. In Comparative Example 1, the coating performance is poor when the cBN powder and the surface of the alloy powder are directly laser clad without preparing the wear-resistant self-lubricating powder. This is mainly because in Comparative Example 1, the cBN powder and the alloy powder are directly mixed by laser cladding to prepare the coating by high temperature input, but the heat input temperature in the laser cladding is too high, and it is difficult to accurately control the occurrence of the conversion from cBN to hBN. In this way, it is difficult to control the content and distribution uniformity of hBN in the coating, and it is difficult to ensure the stability of the coating performance. In the present invention, the cBN powder is pretreated at high temperature to convert the surface of the cBN powder into hBN, so that the single cBN powder becomes a powder in which cBN and hBN coexist after pretreatment (that is, wear-resistant self-lubricating powder is prepared). Then, the above-mentioned cBN and hBN coexisting powder is evenly mixed with the alloy powder and input at high temperature as a coating material to prepare a coating. Since the surface of the cBN powder in the above-mentioned cBN and hBN coexisting powder has been converted into hBN after high-temperature treatment, during laser cladding, basically not too much cBN powder will be converted into hBN, which can effectively control the content and distribution uniformity of hBN in the coating, thereby ensuring the stability of the coating performance.

[0104] By comparing Example 1 with Comparative Example 2, it can be seen that the hardness and friction reduction effect of the coating prepared by the present invention are also much better than the coating performance of the CoCrNi medium entropy alloy.

[0105] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a metal-based wear-resistant self-lubricating coating material, characterized in that: The following steps are involved: Step (1) preparing wear-resistant self-lubricating powder; the wear-resistant self-lubricating powder is a powder obtained by vacuum heating pretreatment of cubic boron nitride powder; the mass content of hexagonal boron nitride in the wear-resistant self-lubricating powder is 10-40%; in step (1), the particle size range of the cubic boron nitride powder is 10-53 μm; The vacuum heating pretreatment is performed at 1200-1400°C for 1.5h-2h; The vacuum degree of the vacuum heating pretreatment is 30-40KPa; The heating rate of the vacuum heating pretreatment is 10°C / min-18°C / min; the cooling rate is 3°C / min-7°C / min; Step (2) preparing a coating material: uniformly mixing the wear-resistant self-lubricating powder and the alloy powder, and drying to obtain a coating material; the alloy powder is at least one of CoCrNi, CoCrFeNi, CoCrFeNiTi, Ti60, and Fe60 alloy systems; The coating material comprises 15-20wt% of wear-resistant self-lubricating powder and 80-85wt% of alloy powder; Step (3) sets the coating material on the surface of the base material, and prepares a metal-based wear-resistant self-lubricating coating material on the base material by laser cladding.

2. The method for preparing the metal-based wear-resistant self-lubricating coating material according to claim 1, characterized in that: Step (2), The particle size of the alloy powder is 15-53 μm; and / or, The alloy powder and the wear-resistant self-lubricating powder are mixed uniformly by ball milling together.

3. The method for preparing the metal-based wear-resistant self-lubricating coating material according to claim 2, characterized in that: The ball milling speed is 300-600 rpm; and / or, The ball milling time is 1.5h-3h; and / or, The ball-to-material mass ratio is 1-10:1; and / or, The drying temperature is 100°C-120°C.

4. The method for preparing the metal-based wear-resistant self-lubricating coating material according to claim 1, characterized in that: In step (3), laser cladding includes the following steps: Step (a): placing a laser head on the surface of the base material to be clad; Step (b): conveying the coating material to the surface of the substrate material to be clad; Step (c): The laser head emits a laser to the surface of the base material to be clad with the coating material, so as to prepare a metal-based wear-resistant self-lubricating coating material on the surface of the base material.

5. The method for preparing the metal-based wear-resistant self-lubricating coating material according to claim 4, characterized in that: Step (a), the distance between the laser head and the surface of the substrate material to be clad is 16-20 mm; and / or, Step (b), the coating material flow rate is 12-14.2 g / min; and / or, Step (c), the laser power is 1800W-2300W; and / or, The wavelength of the laser is 635-650nm; and / or, During laser cladding, the substrate material used is a preheated substrate at a preheating temperature of 400°C-600°C.

6. The method for preparing the metal-based wear-resistant self-lubricating coating material according to claim 1, characterized in that: The mass content of hexagonal boron nitride in the wear-resistant self-lubricating powder is 15-30%.

7. A metal-based wear-resistant self-lubricating coating material prepared according to the method described in any one of claims 1 to 6.

8. Application of the metal-based wear-resistant self-lubricating coating material prepared by the method according to any one of claims 1 to 6 in the fields of aerospace, shipbuilding and automobile.

Citation Information

Patent Citations

  • Preparation method and repairing method of self-lubricating wear-resistant coating of rubber mechanical screw

    CN115491673A

  • Cubic boron nitride composite particle

    US6461990B1